Educational administration a problem-based approach - Cunningham, William G. (Allyn and Bacon, 2000)
The book uses a problem-based approach and provides readers with opportunities to analyze and apply their knowledge to authentic situations. The text includes multiple perspectives that challenge readers to synthesize the material into an effective administrative platform and to make productive choices in arriving at problem solutions. It does not abandon the social science, research, and empirical tradition, but carefully examines moral, ethical, and behavioral implications as well as critical thinking, best practice, and field situated opportunities. Educational Administration presents the major aspects of administration and the complex set of problems and performance assessment challenges that administrators face every day. It emphasizes a number of important challenges like the increasing diversity in our schools and society and the impact of reforms and technology on learning environments. Numerous pedagogical features, philosophical orientations, and emerging lines of inquiry engage readers throughout their explorations and reading assignments.